Resistance to aspergillus flavus and aspergillus parasiticus in almond advanced selections and cultivars and its interaction with the aflatoxin biocontrol strategy - Moral, J.; Garcia-Lopez, M.T.; Gordon, A.; Ortega Beltran, A.; Puckett, R.D.; Tomari, R.; Gradziel, T.M.; Michailides, T. (Scientific Societies, 2022)
Aflatoxin contamination of almond kernels, caused by Aspergillus flavus and A. parasiticus, is a severe concern for growers because of its high toxicity. In California, the global leader of almond production, aflatoxin can be managed by applying the biological control strain AF36 of A. flavus and selecting resistant cultivars. Here, we classified the almond genotypes by K-Means cluster analysis into three groups (susceptible [S], moderately susceptible [MS], or resistant [R]) based on aflatoxin content of inoculated kernels. The protective effects of the shell and seedcoat in preventing aflatoxin contamination were also examined. The presence of intact shells reduced aflatoxin contamination >100-fold. The seedcoat provided a layer of protection but not complete protection. In kernel inoculation assays, none of the studied almond genotypes showed a total resistance to the pathogen. However, nine traditional cultivars and four advanced selections were classified as R. Because these advanced selections contained germplasm derived from peach, we compared the kernel resistance of three peach cultivars to that shown by kernels of an R (Sonora) and an S (Carmel) almond cultivar and five pistachio cultivars. Overall, peach kernels were significantly more resistant to the pathogen than almond kernels, which were more resistant than pistachio kernels. Finally, we studied the combined effect of the cultivar resistance and the biocontrol strain AF36 in limiting aflatoxin contamination. For this, we coinoculated almond kernels of R Sonora and S Carmel with AF36 72 h before or 48 h after inoculating with an aflatoxin-producing strain of A. flavus. The percentage of aflatoxin reduction by AF36 strain was greater in kernels of Carmel (98%) than in those of Sonora (83%). Cultivar resistance also affected the kernel colonization by the biological control strain. AF36 strain limited aflatoxin contamination in almond kernels even when applied 48 h after the aflatoxin-producing strain. Our results show that biocontrol combined with the use of cultivars with resistance to aflatoxin contamination can result in a more robust protection strategy than the use of either practice in isolation.